Analysis of Affecting Factors on the Natural Rubber Exports Volume in North Sumatera - Suri, Tasha Ningtyas; Rahmanta; Wibowo, Rulianda Purnomo (Talenta Publisher, 2021)
North Sumatra is the second largest natural rubber producing province in Indonesia so it has a considerable influence on Indonesia's rubber export activities, however, the export volume of rubber from North Sumatra has fluctuated. The aims of this research were to analyze the factors that influence the volume of natural rubber exports in North Sumatra. The analytical method used is quantitative analysis method in the form of robust regression analysis. The data used in this study are time series data from 1989-2018 using annual data. The results showed that North Sumatra's natural rubber production, natural rubber export price, exchange rate, and inflation simultaneously had a significant and significant effect on the export volume of North Sumatra's natural rubber. North Sumatra natural rubber production, natural rubber export prices, and the exchange rate partially have a real and significant effect on the export volume of natural rubber in North Sumatra, while inflation does not partially affect the export volume of North Sumatra natural rubber.